DIGITALIZATION OF THE ECONOMY AND THE ISSUE OF INEQUALITY IN THE GLOBAL SOCIETY - Đorić, Žarko (International Journal of Economic Practice and Policy, 2024)
Increasing prosperity, as well as the coexistence of persistent and deep inequalities, is one of the greatest paradoxes of our time, which undermines and calls into question global development and modernization processes in today’s world. There is no doubt that the digital revolution is transforming economies on a global scale, bringing with it huge potential economic gains, but also new challenges. In an era of complex environmental, geopolitical, economic and technological risks it is particularly striking so-called growing social fragmentation which is manifested, among other things, through the strong spread of digital inequalities (and the related concept digital divide), which further undermines social cohesion and global cooperation. Although digital progress has created enormous wealth in record time, it has remained concentrated around a small number of individuals, companies and countries, and all predictions are that this trajectory will continue, further deepening already growing inequality. The paper analyzes the inequalities and stratification of the digital sphere and seeks to establish a link between sustainable development, rapid technological change and issues of inequality, and thus encourages debate and reflection on this challenge for researchers and public practitioners in the global context, by applying scientific methods of systematization and analysis. In the coming period, new policies under the auspices of the new agenda will have to respond much better to the new dynamics of the digital economy in order to record more inclusive results in the global world. In a world where more than half of citizens have no or limited internet access, intensive work must be done to close the digital divide (especially in internet access), while inclusiveness would be crucial to building a digital economy that delivers for all, which is crucial for economic mobility and social participation. Collaborative action is needed today to bend the curve of digital transformation towards a more prosperous tomorrow.